2013
DOI: 10.1186/1746-6148-9-157
|View full text |Cite
|
Sign up to set email alerts
|

In vitro prion protein conversion suggests risk of bighorn sheep (Ovis canadensis) to transmissible spongiform encephalopathies

Abstract: BackgroundTransmissible spongiform encephalopathies (TSEs) affect both domestic sheep (scrapie) and captive and free-ranging cervids (chronic wasting disease; CWD). The geographical range of bighorn sheep (Ovis canadensis; BHS) overlaps with states or provinces that have contained scrapie-positive sheep or goats and areas with present epizootics of CWD in cervids. No TSEs have been documented in BHS, but the susceptibility of this species to TSEs remains unknown.ResultsWe acquired a library of BHS tissues and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Disadvantages of the CER assay compared to PMCA include limited amplification of PrP res , additional steps in CER substrate preparation and no known infectivity in the PrP res produced by CER reactions. It is to be noted that in a previous study, however, we found the CER assay resulted in a similar pattern of PrP res formation as that of PMCA 15 . The results presented here also indicate that the CER assay correctly predicts the species barriers for transmission of various TSEs to laboratory mice (Figure 3) and suggest that bobcats may have susceptibility to CWD (Figure 4), in agreement with reports that domestic cats (Felis catus) can acquire prion disease after experimental CWD challenge 26,27 .…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Disadvantages of the CER assay compared to PMCA include limited amplification of PrP res , additional steps in CER substrate preparation and no known infectivity in the PrP res produced by CER reactions. It is to be noted that in a previous study, however, we found the CER assay resulted in a similar pattern of PrP res formation as that of PMCA 15 . The results presented here also indicate that the CER assay correctly predicts the species barriers for transmission of various TSEs to laboratory mice (Figure 3) and suggest that bobcats may have susceptibility to CWD (Figure 4), in agreement with reports that domestic cats (Felis catus) can acquire prion disease after experimental CWD challenge 26,27 .…”
Section: Discussionmentioning
confidence: 49%
“…A number of in vitro assays, based on assessing the conversion of host PrP C to a proteinase K (PK PrP res in pH 7.4 substrate relative to that of the pH 3.5 substrate provides a measure of the species barrier. We have found that the CER assay predicts known species barriers of laboratory mice to various TSEs and have used the assay in efforts to predict the species barrier of numerous mammalian species, including bighorn sheep, to chronic wasting disease (CWD) and other TSEs 14,15 . Investigators interested in a tool allowing rapid screening of TSE species barriers or assessment of PrP C -to-PrP res conversion will find this methodology useful.…”
Section: Introductionmentioning
confidence: 99%
“…While our samples are from Canadian populations of these potentially at-risk species, the data likely represent the spread risk for many in North America. The PrP region has been sequenced in bighorn sheep in the United States from populations in Washington [29], and they found the single haplotype we identified. Similarly for bison, Seabury et al [30] sequenced individuals in four state parks, and found the same genetic variants we identified in the Canadian populations.…”
Section: Discussionmentioning
confidence: 93%
“…However, the potential susceptibility of other, more distantly related species has been suggested by intracerebral inoculation studies and protein conversion assays. Domestic sheep (Ovis aries) are susceptible to CWD by intracerebral inoculation (Hamir et al 2006), and both domestic and bighorn sheep (Ovis canadensis) are potentially susceptible to CWD on the basis of protein conversion assays (Raymond et al 2000;Morawski et al 2013). Species phylogeny and PRNP (prion protein) gene polymorphisms also predict susceptibility of bighorn sheep to CWD (Cullingham et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Species phylogeny and PRNP (prion protein) gene polymorphisms also predict susceptibility of bighorn sheep to CWD (Cullingham et al 2020). Bighorn sheep overlap in range with deer, elk, and moose in parts of western North America, raising concerns for the transmission of CWD from cervids to bighorn sheep (Morawski et al 2013). Additionally, bighorn sheep may be exposed to scrapie, a naturally occurring TSE of domestic sheep and goats (Capra hircus; Greenlee 2019) that has also been recognized in captive mouflon (Ovis orientalis orientalis) sheep (Wood et al 1992a).…”
Section: Introductionmentioning
confidence: 99%